Tyrosine phosphorylation of AAV2 vectors and its consequences on viral intracellular trafficking and transgene expression - Zhong, Li (2008)
We have documented that epidermal growth factor receptor protein tyrosine kinase (EGFR-PTK) signaling negatively affects intracellular trafficking and transduction efficiency of recombinant adeno-associated virus 2 (AAV2) vectors. Specifically, inhibition of EGFR-PTK signaling leads to decreased ubiquitination of AAV2 capsid proteins, which in turn, facilitates viral nuclear transport by limiting proteasome-mediated degradation of AAV2 vectors. In the present studies, we observed that AAV capsids can indeed be phosphorylated at tyrosine residues by EGFR-PTK in in vitro phosphorylation assays and that phosphorylated AAV capsids retain their structural integrity. However, although phosphorylated AAV vectors enter cells as efficiently as their unphosphorylated counterparts, their transduction efficiency is significantly reduced. This reduction is not due to impaired viral second-strand DNA synthesis since transduction efficiency of both single-stranded AAV (ssAAV) and self-complementary AAV (scAAV) vectors is decreased by ~68% and ~74%, respectively. We also observed that intracellular trafficking of tyrosine-phosphorylated AAV vectors from cytoplasm to nucleus is significantly decreased, which leads to ubiquitination of AAV capsids followed by proteasome-mediated degradation, although downstream consequences of capsid ubiquitination may also be affected by tyrosine-phosphorylation. These studies provide new insights into the role of tyrosine-phosphorylation of AAV capsids in various steps in the virus life cycle, which has implications in the optimal use of recombinant AAV vectors in human gene therapy.